Diagnóstico de los niveles de mercurio en empleados y estudiantes de la Facultad de Odontología de La Universidad de Antioquia, 1999 (2001)
ABSTRACT: This descriptive study aims to find the prevalence of mercury intoxication among the students, and employees of the College of Dentistry of the University of Antioquia. This is the first in Colombia that evaluates students and faculty members and not just the auxiliary personnel. Mercury concentrations in 24-hour urine samples were collected and measured with the atomic absorption procedure. The values were read for absorbency and correlated with the Pearson´s correlation coefficient. The 192 samples showed concentrations lower than 30mmg. which is considered the intoxication mark, and 1.6% (3 samples) registerd values equal or higher than 15mmg. which is considered the impregnation limit for the exposed working population. The highest registration, 19mmg corresponded to one faculty member and 2 samples (faculty member and 9th semester student) showed values equal to 15mmg. All the positive results can not be attributed totally to the clinical action carried out in our institution. This fact introduces a confusion variable, imposible to control, since it limits the conclusions. The results are attributed to changes in the handling of mercury. It s expected that this protocol and its methodology will be be replicated in other institutions.